Understanding peacekeeping - Williams, Paul 1975-; Bellamy, Alex J. 1975- (Polity, 2021)
Peace operations remain a principal tool for managing armed conflict and protecting civilians. The fully revised, expanded and updated third edition of Understanding Peacekeeping provides a comprehensive and up-to-date introduction to the theory, history, and politics of peace operations. Drawing on a dataset of nearly two hundred historical and contemporary missions, this book evaluates the changing characteristics of the contemporary international environment in which peace operations are deployed, the strategic purposes peace operations are intended to achieve, and the major challenges facing today’s peacekeepers. All the chapters have been revised and updated, and five new chapters have been added – on stabilization, organized crime, exit strategies, force generation, and the use of force. Part 1 summarizes the central concepts and issues related to peace operations. Part 2 charts the historical development of peacekeeping, from 1945 through to 2020. Part 3 analyses the strategic purposes that United Nations and other peace operations are intended to achieve – namely, prevention, observation, assistance, enforcement, stabilization, and administration. Part 4 looks forward and examines the central challenges facing today's peacekeepers: force generation, the regionalization and privatization of peace operations, the use of force, civilian protection, gender issues, policing and organized crime, and exit strategies
Literaturverzeichnis: Seite 421-459, Register
Keywords: Friedenssicherung; Peacekeeping forces; Global / Peace operations / Friedenssicherung / Friedensichernde Organe / Friedensichernde Streitkräfte / Friedenssicherungsfunktion internationaler Akteure / Internationales Krisenmanagement / Internationale Konfliktprävention / Überblicksdarstellung; Global / Peace operations / Peacekeeping / Peacekeeping bodies / Peacekeeping forces / Peacekeeping function of international actors / International crisis management / International conflict prevention / General overviews; Theorie der Friedenssicherung / Stabilisierung / Schutz von Zivilbevölkerung/Nichtkombattanten in bewaffneten Konflikten; Peacekeeping theory / Stabilization / Protection of civilians/noncombattants in armed conflicts